Concept, features and types of civil legal relations (Bulletin of Kharkiv National University of Internal Affairs, 2023)
It has been established that civil legal relations are social relations between individuals and/or legal entities regulated by the rules of the civil branch of law and arising out of certain tangible and intangible benefits. Attention is drawn to the fact that civil legal relations are regulated not only by the rules of civil law, in particular, this is indicated by such a principle as freedom of contract in civil law. In other words, the content of civil law contracts may go beyond the legal relations provided for by the Civil Code of Ukraine.It has been argued that the key features of such relations are as follows: they may be of property and non-property nature; they are regulated by the rules of the civil branch of law; participants to civil legal relations are equal, i.e., they have the same set of subjective rights and legal obligations; the key principles of legal regulation of civil legal relations are determined at the legislative level, but they are substantively regulated at the contractual level; they arise between private individuals and/or legal entities and are not related to governmental bodies or public institutions; as a rule, civil legal relations are commercial in nature.It has been noted that an important task of the legislator is to create appropriate conditions for the settlement of civil legal relations, since this is an important guarantee of protection of property and non-property rights of a person, and also contributes to the development of the state economy, i.e. is an important element of the functioning of society and the development of the country’s economy.